Neuromodulation zur Schmerztherapie – was ist sinnvoll? - Tronnier, Volker (Fortschritte der Neurologie · Psychiatrie, 2017)
Neuromodulatory techniques have replaced the earlier performed neurolesional procedures to treat chronic pain syndromes with only a few exceptions. Nevertheless these procedures are invasive with respective risks and complications and therefore conservative physical, psychological pharmacological as well as interventional treatments should be performed first. Because this therapy is costly, the indication has to be proven carefully with a strict patient selection and also the long-term results have to be considered. The following paper will give an overview over the recent neuromodulatory techniques, their indications and and published results.
Keywords: chronischer Schmerz; periphere Nervenstimulation; epidurale Rückenmarkstimulation; subkutane periphere Feldstimulation; DRG-Stimulation; intrathekale Medikamentengabe